2012
DOI: 10.1002/hed.22982
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin in elimination of tumor initiating stem‐like and mesenchymal transformation property in head and neck cancer

Abstract: Quercetin suppressing HNC-TICs characteristics may therefore be valuable therapeutics clinically in combination with standard treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…The ability of cancer cells to migrate and invade is increased by the reduction of the expression of E-cadherin, a cell-cell adhesion molecule, whereas the expression of N-cadherin is decreased, which is inversely proportional to that of E-cadherin [42]. Quercetin regulates the expression of EMT markers, such as E-cadherin, vimentin, and β-catenin, in head and neck cancer-derived sphere cells and breast cancer cells [43,44]. In addition, quercetin prevented the EGF-induced expression of N-cadherin and vimentin and increased the expression of E-cadherin in prostate cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of cancer cells to migrate and invade is increased by the reduction of the expression of E-cadherin, a cell-cell adhesion molecule, whereas the expression of N-cadherin is decreased, which is inversely proportional to that of E-cadherin [42]. Quercetin regulates the expression of EMT markers, such as E-cadherin, vimentin, and β-catenin, in head and neck cancer-derived sphere cells and breast cancer cells [43,44]. In addition, quercetin prevented the EGF-induced expression of N-cadherin and vimentin and increased the expression of E-cadherin in prostate cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…[Hsu et al, 2013] In head and neck cancer-derived sphere cells, quercetin (a major polyphenol and flavonoid, commonly detected in many fruits and vegetables) minimizes migration ability partially by decreasing the production of Twist, N-cadherin, and vimentin. [Chang et al, 2013] Thymoquinone (major active ingredient of the plant Nigella sativa ) increases Twist1 promoter methylation resulting in Twist1 downregulation and inhibition of migration, invasion, and upregulation of E-cadherin. [Khan et al, 2015] Imipramine blue promotes degradation of the EMT inducer Twist1 by enhancing F-box and leucine-rich repeat protein 14 (FBXL14)-mediated polyubiquitination mediated destruction of Twist1.…”
Section: Targeting Orchestrators Of Emtmentioning
confidence: 99%
“…[Sadler et al, 2013] Quercetin, a natural polyphenol found in vegetables, reduced migration ability of head partially due to the decreased production of N-cadherin, vimentin and the EMT-TF, Twist1. [Chang et al, 2013]…”
Section: Targeting Effectors Of Emtmentioning
confidence: 99%
“…The increasing interest in the cancer stem cell (CSC) model is dramatically altering the current directions in cancer treatments and drug developments . We identified a subpopulation of oral cancer‐derived CSCs from OSCC cells by sphere formation assay . Oral cancer‐CSCs have been known to have the capacity to promote tumor progression and metastasis, and also contribute to chemoresistance .…”
Section: Introductionmentioning
confidence: 99%
“…3 We identified a subpopulation of oral cancer-derived CSCs from OSCC cells by sphere formation assay. 4 Oral cancer-CSCs have been known to have the capacity to promote tumor progression and metastasis, and also contribute to chemoresistance. [5][6][7][8][9][10][11] Side population technology by Hoechst dye exclusion property is among the successful methodologies for CSC isolation.…”
Section: Introductionmentioning
confidence: 99%